The Criminal Framework for Mental Deception: Controlling Consciousness - Diab, Mohamed Fathi Shehta Ibrahim; Mohamed, Gamal Sayed Khalifa; Al-Shammari, Muhammad bin Saud; Albati, Faris Mohammed; Albkjaji, Mohammed (Journal of Ecohumanism, 2024)
The paper examines some aspects of the legal constructs of mental deception and control over it in the Criminal Codes. Therefore, this research adopts the modest aim of providing an in-depth analysis of how the Criminal Codes go about the business of mental deception in five ways: defining mental deception, the historical development of mental deception, the role of mens rea and knowledge, comparison between different codes, and future legal reform. The research, using a qualitative methodology of case study and legal text analyses, reveals the extent to which the state of practice falls short in current laws. While there continues to be more acceptance of mental deception in the law, much disparity among jurisdictions and, particularly, reforms are urgently needed, this paper concludes that the disparate definitions call for a single, unifying definition in statute law and that there should be admissibility of evidence relating to expertise on psychology for due consideration of such cases in legal proceedings.